PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF PENGENAL HURUF (NARU) BAGI ANAK BA ‘AISYIYAH TALANG KLATEN - Fu’ad Arif Noor; Miati Oktania (QURROTI, 2023)
This study aims to determine the procedure for developing letter recognition interactive learning media in early childhood, as well as determine the feasibility of letter recognition interactive learning media products in early childhood. This research is a type of Research and Development. the ADDIE development model (analysis, design, development and implementation, and evaluation) adapted from Lee & Owens. Data collection techniques were carried out by observation, interviews and questionnaires. The product feasibility testing phase is assessed by media experts and material experts. At the product evaluation stage, an assessment is carried out by the teacher as the first user and students as the second user. This research was conducted at BA `Aisyiyah Talang II with research subjects involving 15 students for field trials before using NARU Interactive Learning Media and after using NARU Interactive Learning Media. The data analysis technique used is a Likert scale. The results of this study are: (1) an interactive learning media model for identifying letters for early childhood that is appropriate for children's learning of basic letter subject matter elements, evaluation practice questions, multimedia objects that support material presentation, consistent layout, visual appearance attractiveness, harmonious color composition, and ease of operation of the program, (2) functional test of interactive learning media for recognizing letters in early childhood including presentation of material, ease of navigation, links, and animation, (3) feasibility assessment by material experts obtaining an average score - an average of 4.66 is included in the very feasible category, the feasibility assessment by media experts obtains an average value of 4.55 which is included in the very feasible category, the assessment of teacher users obtains an average value of 4.61 which is included in the very feasible category.